In vitro inhibition of the growth of glioblastoma by Teucrium polium crude extract and fractions - seyed noureddin nematollahi-mahani; Zohreh Mahdinia; Rana Eftekharvaghefi; Mitra mehrabani; vahid hemayatkhah-jahromi; Fatemeh Nabipour (International Journal of Phytomedicine, 2012)
The cytotoxic effects of Teucrium polium (Lamaceae) have been shown in some studies. However, the antitumor activity of the fractions of this herb has not been studied, neither has the pattern of cell death been evaluated yet. The inhibitory effect of Teucrium polium (T. polium) on U87 cells was evaluated by treatment of U87 cells with various concentrations of crude extract (CE), a petroleum ether (PE) fraction and a diethyl ether (DE) fraction of T. polium for 24 and 48 h. Trypan blue and differential staining were also used to assess the cell viability and the pattern of cell death. CE, PE and DE inhibited cell growth in a dose-dependent manner, and this inhibition was accomplished by necrotic cell death, as assessed by differential staining. The highest inhibitory effect (IC50=64.47) was demonstrated by the PE fraction of T. polium followed by the DE fraction and the CE. Cell death was also higher when U87 cells were treated with PE (P<0.001 compared with other treated groups). Necrotic cells were predominant in all treated groups including CE, PE and DE. The results suggest that the PE fraction of T. polium is the most potent against U87 cells. The antitumor effect of the PE fraction of T. polium is probably executed through the necrotic cell death mechanism.